Legal certainty as a condition for the application of regulations on tax benefits (using the example of the IT industry) - Ponomareva, K. A.; Golovanev, M. A. (Pravoprimenenie, 2025)
Subject. The article examines the challenges of implementing and enforcing industry-specific tax incentives using the example of the IT industry. The specifics of the legal framework governing tax incentives for IT companies, which have undergone significant revisions since 2021, are discussed. Focus is placed on ensuring the availability of instruments providing legal certainty in this area. The purpose of the study. The aim is to identify existing legal issues that limit the application of tax incentives. With regard to the identified gaps in legislation and suboptimal instruments used in establishing IT incentives, measures are proposed to address the situation and increase legal certainty. Methodology. The emphasis is placed on using general scientific methods, such as analysis and synthesis, as well as specific scientific methods like the formal legal method and the method of legal modeling. Conclusions. It is concluded that there are few effective mechanisms in the legislation to address promptly the legal uncertainty arising when implementing tax incentives for IT companies. The legal aspects of the qualification of an IT company established within a group as an artificial structure separated for the purpose of applying tax incentives are discussed. The issue of suboptimal structures for current limitations on income derived from IT activities has been identified, and proposals for resolving this issue have been made, including through improvements to tax legislation. The sections 1 and 2 were contributed by K.A. Ponomareva (section 2 in collaboration with M.A. Golovanev), sections 2-6 by M.A. Golovanev (section 2 in collaboration with K.A. Ponomareva).